Regio‐ and Diastereoselective Formal [2+2] Cycloaddition of Allenes with Amino‐Functionalized Alkenes by Rare‐Earth‐Catalyzed C(sp2)−H Activation. (10th October 2022) - Xu, Wenxuan; Cong, Xuefeng; An, Kun; Lou, Shao‐Jie; Li, Zhenghua; Nishiura, Masayoshi; Murahashi, Tetsuro; Hou, Zhaomin
Abstract: The [2+2] cycloaddition of allenes with alkenes is of much interest and importance as a straightforward route for the construction of four‐membered carbocycles but has remained much underexplored to date. Herein we report for the first time the intermolecular regio‐ and diastereoselective formal [2+2] cycloaddition of a wide range of allenes with amino‐functionalized alkenes by half‐sandwich rare‐earth catalysts. The reaction proceeded through an allene C(sp 2 )−H activation mechanism initiated by the site‐selective deprotonation of the allene unit by a rare‐earth metal alkyl species followed by alkene insertion into the resulting metal‐allenyl bond and the subsequent intramolecular cycloaddition to an allene C=C bond. This protocol offers a unique route for the synthesis of a new family of cyclobutane and cyclobutene derivatives which were difficult to access previously. Abstract : Half‐sandwich rare‐earth catalysts serve as a unique platform for the regio‐ and diastereoselective formal [2+2] cycloaddition of a wide range of allenes with amino‐functionalized alkenes via allene C(sp 2 )−H activation, affording a new family of cyclobutane and cyclobutene derivatives which were difficult to access previously.